DEVELOPMENT OF PROBLEM-BASED DIGITAL GAME AS DIGESTIVE SYSTEM LEARNING MATERIAL - Solagratia Akollo; Desy Fajar Priyayi; Marisa Christina Tapilouw (EDUSAINS, 2022)
This research aims to 1) develop the problem-based digital game learning media to improve students' cognitive learning outcomes, 2) find out the feasibility of the use of the problem-based digital game learning media, and 3) determine the increase in students’ cognitive learning outcomes after using the problem-based digital game learning media. This development research used the 4-D model (Four D) which consisted of 4 stages of define, design, develop, and disseminate. The research instrument were validation sheets, interview sheet, and questionnaire. The data were analyzed using quantitative and descriptive qualitative analysis. The result of the development was the digital game learning media. The results of the validation showed a score of 85.3% (very feasible) for media, 92.3% (very feasible) for content. Meanwhile, it reached a score of 81.25 % (very feasible) from the pedagogical expert validation, 92 % (very feasible) from practitioner validation, 90,42 % (very feasible) and 92.1% (very feasible) from students. The N-Gain analysis showed students in the high (90%) and moderate (10%) results. The results of the study show that the digital game is very suitable to be used in the learning process.AbstrakPenelitian ini bertujuan untuk: 1) mengembangkan media pembelajaran game digital berbasis masalah untuk meningkatkan hasil belajar kognitif siswa, 2) mengetahui kelayakan game digital berbasis masalah, serta 3) mengetahui peningkatan hasil belajar kognitif siswa yang menerapkan media pembelajaran game digital berbasis masalah. Penelitian ini merupakan penelitian pengembangan dengan model 4-D (Four D). Model pengembangan 4-D terdiri atas 4 tahap yaitu define (pendefinisian), design (perancangan), develop (pengembangan), dan disseminate (penyebarluasan). Intrumen pengumpulan data terdiri dari lembar validasi, lembar wawancara, dan angket. Teknik analisis data dilakukan secara deskriptif kuantitatif dan kualitatif. Hasil validasi media memperoleh skor sebesar 85,3 % (sangat layak), validasi materi memperoleh skor sebesar 92,3 % (sangat layak), validasi ahli pedagogi memperoleh skor sebesar 81,25 % (sangat layak), validasi praktisi memperoleh skor sebesar 92% (sangat layak), sedangkan hasil validasi terhadap siswa diperoleh skor sebesar 90,42 (sangat layak) dan 92,1% (sangat layak). Berdasarkan analisis N-Gain diperoleh hasil siswa dengan kategori tinggi (90%) dan sedang (10%). Hasil penelitian menunjukan bahwa game digital berbasis masalah sangat layak digunakan dalam proses pembelajaranHow To Cite: Akollo, S., Priyayi, D.F., Tapilouw, M.C. (2022). Development of Problem-Based Digital Game as Digestive System Learning Material. EDUSAINS, 14 (2) : 148-161.